Making visible young people from Villa La Angostura and their labor insertion - Arcidiácono, María Laura (2019)
This work represents a continuation of the Final Integrative Report of the Specialization Career on Educational and Occupational Guidance (post-degree Secretariat, Psychology School, UNLP) “Guidance strategies to young people of the Program Youth with More and Better Jobs from Villa La Angostura – How do the young from the program choose and in what context do they carry out such choices?” (hereinafter referred to M&BJP) (Arcidiácono, 2017). The purpose of this investigation, focused on young participants from M&BJP, is to examine the factors that affect the difficulties to reach and support educational and work possible projects in their town and to analyze the guidance strategies applied / possible to be applied in educational guidance in this context. This investigation, carried out in 2018, allowed expanding the analyzed sample by means of an open interview, reporting that the results provided by the previous research are not only about the young of the program. Therefore, it is possible to assert that labor insertion of young population of this town is an issue that does not only depend of the political, economic and social situation of the country, but also it has specific characteristics and determinants of Villa La Angostura, and must be attended by the Municipality.